2009
DOI: 10.1124/dmd.108.026112
|View full text |Cite
|
Sign up to set email alerts
|

Utility of MetaSite in Improving Metabolic Stability of the Neutral Indomethacin Amide Derivative and Selective Cyclooxygenase-2 Inhibitor 2-(1-(4-Chlorobenzoyl)-5-methoxy-2-methyl-1H-indol-3-yl)-N-phenethyl-acetamide

Abstract: ABSTRACT:Prediction of the metabolic sites for new compounds, synthesized or virtual, is important in the rational design of compounds with increased resistance to metabolism. The aim of the present investigation was to use rational design together with MetaSite, an in silico tool for predicting metabolic soft spots, to synthesize compounds that retain their pharmacological effects but are metabolically more stable in the presence of cytochrome P450 (P450) enzymes. The model compound for these studies was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The method uses flexible molecular interaction fields generated by GRID to determine the probability of an atom being the site of metabolism. Previous studies indicated that MetaSite's first three ranked predictions were experimentally confirmed for about 84% of the cases [12,[18][19][20]. The method not only predicts the metabolic soft spots of a compound, but also highlights the molecular moieties that help to direct the molecule in the cytochrome cavity such that the site of metabolism is in proximity to the catalytic center.…”
Section: Model Interpretationmentioning
confidence: 90%
See 1 more Smart Citation
“…The method uses flexible molecular interaction fields generated by GRID to determine the probability of an atom being the site of metabolism. Previous studies indicated that MetaSite's first three ranked predictions were experimentally confirmed for about 84% of the cases [12,[18][19][20]. The method not only predicts the metabolic soft spots of a compound, but also highlights the molecular moieties that help to direct the molecule in the cytochrome cavity such that the site of metabolism is in proximity to the catalytic center.…”
Section: Model Interpretationmentioning
confidence: 90%
“…The metabolic soft spots of the resulting compounds were predicted with MetaSite [12,22]. Although this method is not designed to predict the relative rate of metabolism of a compound, the identification of the metabolic soft spots could serve as a useful guide for designing [12,[18][19][20] have described success rate of 84% in predicting the correct site of metabolism when its top three predictions are considered. Thus, we visualized the first three ranked predicted soft spots for each of the unstable compounds and identified some substructures that always contained predicted soft spots.…”
Section: Fragment Miningmentioning
confidence: 99%
“…The MetaSite computational procedure was used to predict the most likely sites of 6 metabolism and the structures of its metabolites [27,28]. The plot of MetaSite in silico predictions for sites of metabolism for compound 6 by liver model is shown below (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This relationship may be due to binding to plasma proteins which is expected to increase with larger log P 7.4 values of the indomethacin analogs. 30) These radiotracers likely bind to the plasma proteins similar to other NSAIDs, including indomethacin binding with high affinity to serum albumin. 31,32) Non-specific binding to albumin and other plasma proteins is known to correlate positively and linearly in vitro with increasing lipophilicity.…”
mentioning
confidence: 99%